The effect of Vermicompost and NPK Mutiara Fertilizers 16:16:16 on the growth and yield of water spinach plants (Ipomea Reptans Poir) - Syahidin, Nadhil; Subarja, Indra Darmawan; Alfil, Muhamad; Faqih, Achmad (Indonesian Journal of Multidisciplinary Science, 2024)
Water spinach (Ipomoea reptans Poir.) is a short-lived plant that is highly nutritious, containing vitamins A, B, and C, protein, calcium, phosphorus, sitosterol, and minerals, especially iron, which are beneficial for body growth and health. The objectives of this study are to determine the significant interaction between organic (vermicompost) and inorganic (NPK) fertilizers on the growth and yield of water spinach and to identify the optimal dosages of vermi-compost and NPK fertilizers that have the best effect on its growth. The study was conducted in Tegalsari Village, Plered District, Cirebon Regency, West Java Province. The research was conducted using a Randomized Block Design (RBD) with a factorial pattern consisting of two factors: the dose of VermiCompost (K) and the dosage of NPK (N) Mutiara 16:16:16 (N). The results showed that a combination of rice straw compost at 14 tons/ha and 200 kg/ha of the NPK was found to be the best dose for achieving the highest values for plant height, number of leaves, leaf area, and fresh weight of the plants at 24 days after planting (DAP). The best results were achieved with the combination of K3 and N3 treatments, which provided the best results in terms of plant height and leaf area.